2015
DOI: 10.1039/c4cy00663a
|View full text |Cite
|
Sign up to set email alerts
|

Striking difference between alkane and olefin metathesis using the well-defined precursor [Si–O–WMe5]: indirect evidence in favour of a bifunctional catalyst W alkylidene–hydride

Abstract: Metathesis of linear alkanes versus olefins using supported multifunctional catalyst gives a very striking different distribution of metathesis products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…6 supported silica and silica-alumina catalysts and their application in alkane metathesis reaction were already reported by our group [14,20]. During the alkane metathesis reaction we observed that silica and silica-alumina supported catalysts are very efficient as compared to Ta-H supported catalyst for alkane metathesis reaction [22,24,25]. Note that W-based catalysts are better metathesis catalysts than the Ta catalysts.…”
Section: Evolution Of Hydro-metathesis Reaction W(ch 3 )supporting
confidence: 64%
“…6 supported silica and silica-alumina catalysts and their application in alkane metathesis reaction were already reported by our group [14,20]. During the alkane metathesis reaction we observed that silica and silica-alumina supported catalysts are very efficient as compared to Ta-H supported catalyst for alkane metathesis reaction [22,24,25]. Note that W-based catalysts are better metathesis catalysts than the Ta catalysts.…”
Section: Evolution Of Hydro-metathesis Reaction W(ch 3 )supporting
confidence: 64%
“…Interestingly, we also found that the reaction of saturated FAE (as the ethyl undecylate) with 1 did not produce alkane metathesis products at 150°C for 3 days period. This result can be rationalized by considering the possible coordination of a W-methylidene hydride, propagative species in alkane metathesis, 12 into the functional ester group. And, this would prevent two crucial steps in the alkane metathesis: the C-H alkane activation required for the olefin intermediate and the release of catalytic amount of hydrogen.…”
Section: Ethyl Undecylenate Metathesis Catalyzed By Silica Supported mentioning
confidence: 99%
“…10 This precursor catalyzes the metathesis of alkanes into lower and higher homologues: cyclooctane is transformed into macrocyclic alkanes 11 and linear alkanes are converted into higher and lower linear alkanes. 12 As during this alkane metathesis process olefins are formed in minute amount, 13 we also examined the reactivity of terminal olefins with W-based catalysts supported on silica. 12 For instance, 1-decene is transformed into a distribution of linear terminal and internal olefins (up to C30 olefins) through successive reactions of isomerization and metathesis (ISOMET).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations